Molecular simulation of pentaethylene glycol monooctyl ether micelles in water. Prediction of the micellization Gibbs energy - Navarro-Aquino, David; Medeiros, Milton (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
The Gibbs energy (Δg0) and the enthalpy (Δh0) of the micellization of pentaethylene glycol monooctyl ether (C8E5) were predicted by molecular dynamics (MD) simulations of preformed micelles of various sizes at 298.15 K. Macroscopically, the equilibrium size distributions of the micellar aggregates in amphiphile solutions were modeled using a multiple chemical equilibrium approach, under the assumption that the micelles are spheres or sphero-cylinders. In the model, Δg0 is a function of the micelle size, and the parameters for its determination are related to the contributions of the amphiphiles on the micelle’s spherical caps and cylindrical body. To estimate these contributions, the thermodynamic integration technique was employed over the MD simulations. For Δg0, the predicted parameters are very similar to those determined by fitting the macroscopic model to measured tensiometric and calorimetric data. However, Δh0 was underpredicted compared to experimental data. The parameters calculated via MD allowed the prediction of the critical micelle concentration and of the mean aggregation number, in very good agreement with those previously published from experimental calorimetric and tensiometric data. [Display omitted]